African weakly electric fishes of the genus Petrocephalus (Osteoglossomorpha: Mormyridae) of Odzala National Park, Republic of the Congo (Lékoli River, Congo River basin) with description of five new species - Lavoué, Sébastien; Sullivan, John P.; Arnegard, Matthew E. (Zootaxa, 2010)
Here we examine new collections of Petrocephalus species (Osteoglossomorpha: Mormyridae: Petrocephalinae) made within Odzala National Park in the Republic of the Congo (Lékoli River drainage, northwestern Congo River basin). We compare these collections to type material of all nominal Petrocephalus species described from the Congo basin and the adjacent Lower Guinea ichthyofaunal province. Based on morphology and electric signal characteristics we recognize eleven distinct species of Petrocephalus in these collections, including five new species described herein: Petrocephalus binotatus, Petrocephalus zakoni n. sp., Petrocephalus valentini n. sp., Petrocephalus balayi, Petrocephalus microphthalmus, Petrocephalus odzalaensis n. sp., Petrocephalus christyi, Petrocephalus sauvagii, Petrocephalus pulsivertens n. sp., Petrocephalus grandoculis and Petrocephalus mbossou n. sp. Each species can be distinguished by a combination of characters, the most important of which are numbers of dorsal and anal fin rays, mouth width, eye size, number of upper jaw teeth and melanin markings. Electric signal waveform characteristics are useful for diagnosing a few of the species. The eleven Petrocephalus species of the Odzala assemblage appear to be reproductively isolated biological species based on genetic evidence we have gathered from the mitochondrial cytochrome b gene. Our study of Petrocephalus type material reveals that Petrocephalus guttatus was erroneously assigned to this genus; we now assign this species to Pollimyrus within the sister subfamily, Mormyrinae. Additionally, we provide a dichotomous key to the eleven Petrocephalus species of Odzala National Park.